Finding suitable acid for acidizing of low permeable sandstone formation: A research - Shafiq, M.U. (Society of Petroleum Engineers, 2013)
As more technologies to enhance oil production recovery are being developed, well stimulation has been introduced and it acts as one of the important roles to fulfil the demand of world for energy. Well stimulation is a well intervention performed on an oil or gas well to increase production by improving the flow of hydrocarbons from the drainage area into the well bore. Well stimulation generally uses fluids which create or enlarge the flow channels of formation so that it can overcome low permeability of formation. A most common and one of the most successful well stimulation is matrix acidizing. In matrix acidizing, acids are injected at matrix pressure below formation fracturing pressure. The permeability of formation will be increased either by removing the pore-plugging materials in the formation or by creating new or enlarged flow paths in the rock depending on the formation and acid types. The right type of acid or combination of acids must be used to remove the damage. Thus, careful acid choice and treatment design are critical for a successful matrix acidizing. This paper presents the results of laboratory investigation of different acid combinations: HF/HCl, HF/HCOOH, HF/H3PO4, HBF4/HCl and HBF4/HCOOH. Hydrofluoric acid and fluoboric acid are used to dissolve clays and feldspar, while hydrochloric acid, phosphoric acid and formic acid are added to control the speed of reaction to allow the maximum acid to penetrate the core sample and also act as a buffer to maintain pH of the solution. Different tests have been performed on the core samples before and after the acidizing to do the comparative study. The results analyzed are permeability, porosity, color change, strength and mineralogy. Most of the new combinations used in this research showed better results than mud acid. But overall it is clear that in coming future lot of work can be done on sandstone acidizing prospects. Â© 2013, Society of Petroleum Engineers.